Simeprevir plus sofosbuvir (12 and 8 weeks) in hepatitis C virus genotype 1‐infected patients without cirrhosis: OPTIMIST‐1, a phase 3, randomized study. Issue 2 (22nd March 2016) - Kwo, Paul; Gitlin, Norman; Nahass, Ronald; Bernstein, David; Etzkorn, Kyle; Rojter, Sergio; Schiff, Eugene; Davis, Mitchell; Ruane, Peter; Younes, Ziad; Kalmeijer, Ronald; Sinha, Rekha; et al.
Abstract : Effective antiviral therapy is essential for achieving sustained virological response (SVR) in hepatitis C virus (HCV)‐infected patients. The phase 2 COSMOS study reported high SVR rates in treatment‐naive and prior null‐responder HCV genotype (GT) 1‐infected patients receiving simeprevir+sofosbuvir±ribavirin for 12 or 24 weeks. OPTIMIST‐1 (NCT02114177) was a multicenter, randomized, open‐label study assessing the efficacy and safety of 12 and 8 weeks of simeprevir+sofosbuvir in HCV GT1‐infected treatment‐naive and treatment‐experienced patients without cirrhosis. Patients were randomly assigned (1:1; stratified by HCV GT/subtype and presence or absence of NS3 Q80K polymorphism [GT1b, GT1a with Q80K, GT1a without Q80K]), prior HCV treatment history, and IL28B GT [CC, non‐CC]) to simeprevir 150 mg once daily+sofosbuvir 400 mg once daily for 12 or 8 weeks. The primary efficacy endpoint was SVR rate 12 weeks after end of treatment (SVR12). Superiority in SVR12 was assessed for simeprevir+sofosbuvir at 12 and 8 weeks versus a composite historical control SVR rate. Enrolled were 310 patients, who were randomized and received treatment (n = 155 in each arm). SVR12 with simeprevir+sofosbuvir for 12 weeks (97% [150/155; 95% confidence interval 94%‐100%]) was superior to the historical control (87%). SVR12 with simeprevir+sofosbuvir for 8 weeks (83% [128/155; 95% confidence interval 76‐89%]) was not superior to the historical control (83%). The most frequent adverse events were nausea, headache, and fatigue (12‐week arm: 15% [23/155], 14% [22/155], and 12% [19/155]; 8‐week arm: 9% [14/155], 17% [26/155], and 15% [23/155], respectively). No patients discontinued treatment due to an adverse event. One (1%, 12‐week arm) and three (2%, 8‐week arm) patients experienced a serious adverse event (all unrelated to study treatment). Conclusion : Simeprevir+sofosbuvir for 12 weeks is highly effective in the treatment of HCV GT1‐infected patients without cirrhosis, including those with Q80K. (Hepatology 2016;64:370‐380)